Pengaruh Disiplin Kerja terhadap Efektivitas Kerja Petugas Apron Movement Control (AMC) di Bandar Udara Internasional Soekarno Hatta - Ni Luh Riyani Artha Saputri; Hodi Hodi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The success of operational management at an airport is highly dependent on the performance and discipline of the Apron Movement Control (AMC) officers (Nurifi, 2024). AMC officers are required to be able to carry out high discipline, considering the many safety procedures that must be followed in order to avoid potential risks and incidents, because this affects the effectiveness of work and also the efficiency of airport officers, namely Apron Movement Control (AMC). The purpose of this study was to determine whether there is an influence of work discipline on the effectiveness of the work of Apron Movement Control (AMC) officers at Soekarno-Hatta International Airport and how much influence it has. This study uses a quantitative approach. The location of the research was carried out at Soekarno-Hatta International Airport, Benda District, Tangerang City and Kosambi, Tangerang, Banten. With a research period of August 2024 to February 2025. In this study, all Apron Movement Control (AMC) officers at Terminal 3 of Soekarno-Hatta International Airport, totaling 19 people, will be used as respondents by filling out the questionnaire provided. Based on the results of the research and analysis that have been conducted, it can be concluded that work discipline has a significant influence with a contribution of 75.9%. Meanwhile, the remaining 24.1% is influenced by other factors that were not analyzed in this study. This influence is proven by the coefficient of determination (R²) value of 0.759, which shows that work discipline contributes 75.9% to the effectiveness of the Apron Movement Control (AMC) officers at Soekarno-Hatta International Airport.